Thermally Activated Delayed Fluorescent Dendrimers that Underpin High‐Efficiency Host‐Free Solution‐Processed Organic Light‐Emitting Diodes (Adv. Mater. 23/2022). Issue 23 (9th June 2022) - Sun, Dianming; Duda, Eimantas; Fan, Xiaochun; Saxena, Rishabh; Zhang, Ming; Bagnich, Sergey; Zhang, Xiaohong; Köhler, Anna; Zysman‐Colman, Eli
Abstract : Dendrimer Emitters In article number 2110344, Dianming Sun, Xiaohong Zhang, Anna Köhler, Eli Zysman‐Colman, and co‐workers report the rational design of thermally activated delayed fluorescence (TADF) dendrimer emitters that show remarkable photophysical properties, resolving the conflicting requirements of achieving simultaneously a small activation energy and a large oscillator strength. Their use in a host‐free solution‐processed organic light‐emitting diode (OLED), which shows record‐high external quantum efficiencies, is demonstrated. The dendrimer design strategy provides a route to high‐performance solution‐processed TADF OLEDs and evidences the full potential of dendrimers as emissive materials.